Theoretical bases of employment of women that were convicted to imprisonment in Ukraine - Неживець, Олена Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In the article the questions of labour and employment of zasudzhenikh are examined in establishments of implementationof punishments and recommendations are given in relation to the improvement of the use of labourof zasudzhenikh.